INNOVATIONS IN THE EDUCATIONAL SYSTEM (Academicia Globe: Inderscience Research, 2023)
In this article, we will explore the innovations in the educational system. The article will cover the different methods used to improve education, the results of these methods, and their impact on students. The article will conclude with a discussion on the future of education and provide suggestions for further innovation.